The chronic cough enigma : acid reflux, asthma, and recalcitrant cough : the path to a cure - Koufman, Jamie (Katalitix Media, 2014)
Presents a path to curing chronic cough of a non-pulmonary nature that draws from the study of fifty chronic cough patients, presenting histories, findings, and diagnostic test results.